Strong but permeable barriers to gene exchange between sister species of Epidendrum - Pinheiro, Fabio; Melo E Gouveia, Tiago Manuel Zanfra de; Cozzolino, Salvatore; Cafasso, Donata; Cardoso-Gustavson, Poliana; Suzuki, Rogerio Mamoru; Palma-Silva, Clarisse [UNESP] (Botanical Soc Amer Inc, 2016)
PREMISE OF THE STUDY: The investigation of reproductive barriers between sister species can provide insights into how new lineages arise, and how species integrity is maintained in the face of interspecific gene flow. Different pre- and postzygotic barriers can limit interspecific gene exchange in sympatric populations, and different sources of evidence are often required to investigate the role of multiple reproductive isolation (RI) mechanisms. METHODS: We tested the hypothesis of hybridization and potential introgression between Epidendrum secundum and Epidendrum xanthinum, two Neotropical food-deceptive orchid species, using nuclear and plastid microsatellites, experimental crosses, pollen tube growth observations, and genome size estimates. KEY RESULTS: A large number of hybrids between E. secundum and E. xanthinum were detected, suggesting weak premating barriers. The low fertility of hybrid plants and the absence of haplotype sharing between parental species indicated strong postmating barriers, reducing interspecific gene exchange and the development of advanced generation hybrids. Despite the strength of reproductive barriers, fertile seeds were produced in some backcrossing experiments, and the existence of interspecific gene exchange could not be excluded. CONCLUSIONS: Strong but permeable barriers were found between E. secundum and E. xanthinum. Indeed, haplotype sharing was not detected between parental species, suggesting that introgression is limited by a combination of genic incompatibilities, including negative cytonuclear interactions. Most taxonomic uncertainties in this group were potentially influenced by incomplete RI barriers between species, which mainly occurred sympatrically.
Keywords: assignment tests; cytonuclear incompatibility; hybridization; introgression; Orchidaceae; pollen-pistil interaction; postzygotic barriers; reproductive isolation; speciation; species delimitation